Polymer structure characterization : from nano to macro organization in small molecules and polymers - Pethrick, R. A. (Richard Arthur), 1942- (Cambridge, UK : RSC Publishing, 2014)
The different physical properties displayed by low molar mass organic materials and polymers are a result of their molecular organization. In order to understand the structure property relationship of a material it is necessary to first look at the interactions at a molecular level. This new edition of Polymer Structure Characterization provides readers with the background needed to understand the factors that influence molecular organization and how this affects the morphology and bulk physical properties of a material. In order to introduce the concepts, the book first looks at small molecular systems and builds up to complex macromolecular systems.
Includes bibliographical references and index.
Keywords: Molecular structure; Polymers